TANGGUNG JAWAB RISIKO KERUSAKAN RUMAH KONTRAKAN - T. Sabirin (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2022)
This study aims to determine the form of the rental house agreement and the form of responsibility for the risk of damage to the rented house without an initial agreement in Sigli City District. This research uses descriptive analysis method, using observation, interview and documentation techniques. The results showed that the form of the rental house agreement in the Sigli City District was carried out by both parties between the owner and the tenant verbally or not in writing with a meeting between the two parties by discussing the price of the house without any other regulations. The form of responsibility for the risk of damage in the Kota Sigli District is carried out by both parties which is carried out by means of good deliberation, does not occur between the two, but if it cannot be resolved by deliberation, it can be resolved by means of civil law.